A construção do ethos de “não-político” no discurso eleitoral de João Doria - Santos, Mateus da Cunha (2020)
In recent years, people with consolidated careers in areas such as entertainment, sports and entrepreneurship have disputed political power and won significant victories in several countries, like the businessman and television presenter Donald Trump, sworn in as President of the USA in 2017, the jurist Giuseppe Conte, who became Prime Minister of Italy in 2018, and the comedian Volodymyr Zelensky, sworn in as President of Ukraine in 2019. In Brazil, one of the exponents of this “movement” of outsiders in politics is the businessman João Doria, elected mayor of São Paulo in 2016, after a campaign focused on building a personal image that confronts the professional politician. Given this scenario, our research key question is: how is the ethos of “non-political” constructed in João Doria's electoral discourse? To answer this question, the main objective of this essay was to analyze the construction of the “non-political” ethos in João Doria's electoral discourse. The primary corpus of analysis was formed by 8 electoral programs displayed on São Paulo city Electoral Propaganda Free Time (HGPE) from august 26 to september 29, 2016, and 10 commercials daily displayed over the same period on local televisions stations. To have a better understanding of how the “non-political” ethos was constructed and compare possible similarities and differences in the approaches, we extended the analysis to the 2018 election campaign, in which the candidate ran for governor of São Paulo. The selected corpus consisted of 8 electoral programs and 8 commercials from the first round of the election and 8 electoral programs and 3 commercials of the second round. The Discourse Analysis (AD) method was used to interpret the collected data, based on approaches by Maingueneau (2008a, 2008b, 2015) and Charaudeau (2015, 2016). Among the results obtained, we highlight that the “non-political” ethos is constructed mainly through the figures of rich, celebrity, worker, manager and hero, associated with the most diverse personal attributes. The scenarios analyzed also revealed that the figures of “antipetist” and “BolsoDoria” also refer to that ethos, since they present another striking facet of the “non-politician”, which is the antipolitism reinforced by an accentuated patriotism, to the point that Doria even attended national protests against politicians and embodied the ethos of a markedly anti-establishment candidate.